Profiles and correlation between sprint and agility k-test of elite young soccer players as a function of age - Cabell, L.; Zahalka, F.; Maly, T.; Mala, L.; Dragusky, M.; Baca, A. (Medicine & Science in Sports & Exercise, 2018)
PURPOSE: To determine the profiles and relationship between linear running speed and agility KT of elite young soccer players. METHODS: Elite Czech national level young male soccer players volunteered for his study and were divided into four age groups (16 yr, n1 = 22; 17 yr, n2 = 18; 18 yr, n3 = 26; 19 yr, n4 = 20). The KT consisted of the participants running at maximum speed between cones positioned in a "K" pattern on a field with artificial grass. The participants started and ended running at the intersection of the "K" pattern. A contact switch for time measurement was placed on the top of each cone which participants touched with the hand. The participants performed two trials and the time of test execution was measured in seconds. Times were measured in a 5-m (S5) and 10-m (S10) dash from a static position. Two-way (4x2) ANOVA and post-hoc Tukey HSD were used for statistical assessment. Pearson correlation coefficient test was used to correlate two dependent variables. P<.05. RESULTS: Factorial ANOVA indicated no significant interaction between sprint distance and age, F 3, 164=0.15, p=.93, but significant main effect for sprint distance, F 1, 164=2142.61, p<.01, and age, F 3, 164=3.06, p<.05. The 19-year old group significantly improved both sprint times compared to the other age groups. The correlation between sprint times and KT for individual age groups primarily showed weak to moderate non-significant correlations: 16 yr: rS5=-0.24, NS; rS10=0.24, NS; 17 yr: rS5=0.46, NS; rS10=0.39, NS; 18 yr: rS5=0.22, NS; rS10=0.46, p<.05; 19 yr: rS5=0.36, NS; rS10=0.36, NS. The correlation between sprint times for S5 and S10 for the individual age groups: 16 yr: r = 0.64, p<.01; 17 yr: r = 0.76, p<.01; 18 yr: r = -0.06, NS; 19 yr: r = 0.97, p<.01. CONCLUSION: The sprint distance main effect indicated that sprint times improve with participants` ages. The weak correlation between sprint and KT may suggest a different training program for young soccer athletes or individual training program for different ages. The significant correlation between the linear sprint distances shows a good choice for speed training.